Characterization of transposon Tn1528, which confers amikacin resistance by synthesis of aminoglycoside 3'-O-phosphotransferase type VI. - Lambert, T (1994)
Providencia stuartii BM2667, which was isolated from an abdominal abscess, was resistant to amikacin by synthesis of aminoglycoside 3'-O-phosphotransferase type VI. The corresponding gene, aph(3')-VIa, was carried by a 30-kb self-transferable plasmid of incompatibility group IncN. The resistance gene was cloned into pUC18, and the recombinant plasmid, pAT246, was transformed into Escherichia coli DH1 (recA) harboring pOX38Gm. The resulting clones were mixed with E. coli HB101 (recA), and transconjugants were used to transfer pAT246 by plasmid conduction to E. coli K802N (rec+). Analysis of plasmid DNAs from the transconjugants of K802N by agarose gel electrophoresis and Southern hybridization indicated the presence of a transposon, designated Tn1528, in various sites of pOX38Gm. This 5.2-kb composite element consisted of aph(3')-VIa flanked by two direct copies of IS15-delta and transposed at a frequency of 4 x 10(-5). It therefore appears that IS15-delta, an insertion sequence widely spread in gram-negative bacteria, is likely responsible for dissemination to members of the family Enterobacteriaceae of aph(3')-VIa, a gene previously confined to Acinetobacter spp.